Antibacterial Activity of Bifidobacterium breve Against Clostridioides difficile - Yang, Jingpeng; Yang, Hong (Frontiers in Cellular and Infection Microbiology, 2019)
Bifidobacterium breve (YH68) is widely used in the fields of food fermentation and biomedicine. In this study, we explored the antibacterial activity of the cell free culture supernatant (CFCS) of YH68 against C. difficile ATCC 9689 (CD) by measuring multiple indexes, including the growth, spores production, toxin A/B production, and the expression levels of the tcdA and tcdB genes of CD. In addition, we examined the changes in major cellular functional groups, structures, permeability, integrity, and the proton motive force (PMF) of the cytoplasmic membrane. The results showed that double-dilution ratio of YH68-CFCS (3×109 CFU/mL) was the MIC value. The cell density, spores production and the toxin production of CD treated with YH68-CFCS were lower than that of the control (p<0.05). In addition, the gene expression levels of tcdA and tcdB in CD treated with YH68-CFCS were significant downregulated (p<0.05). Marked differences were observed in the cell membrane components, such as amino acids, fatty acids, and polypeptides, as well as in the polysaccharide skeleton of the cell well, by FT-IR spectroscopy and SEM. Analysis of the cell membrane permeability and integrity of the CD cells revealed that YH68-CFCS induced the leakage of a large amount of intracellular K+, inorganic phosphate, ATP, nucleic acids and proteinaceous substances. Furthermore, PMF analysis indicated that there was a significant change in Δψ and ΔpH. These findings demonstrated that the antibacterial activity of YH68-CFCS against CD involved the inhibition of growth, spore production, toxin production and virulence genes expression; a consumption of PMF in the cytoplasmic membrane, the formation of pore in the cell membrane, together with the enhanced cell membrane permeability; and, eventually, cell completely disintegration.